2015
DOI: 10.2147/tcrm.s87162
|View full text |Cite
|
Sign up to set email alerts
|

A case of Descemet’s membrane detachments and tears during phacoemulsification

Abstract: Descemet’s membrane detachment is an important reason for corneal endothelial decompensation after intraocular surgery. During cataract surgery, it is an unusual complication. We report a case of Descemet’s membrane detachment in which approximately 60% of Descemet’s membrane (DM) involving approximately the upper two-thirds of the cornea was torn out during a routine phacoemulsification. It caused diffuse corneal edema and blurred vision in the 2 months following the surgery. Topical prednisolone acetate (1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The incidence of significant sight-threatening DMD after phacoemulsification was 0.044% to 0.52% [ 14 , 15 ]. Improper operation of instrument entry into the anterior chamber is the most significant cause of DMD following phacoemulsification [ 18 ]. Although postoperative visual acuity and corneal thickness returned to normal levels afterward, the corneal endothelial cell density decreased by 30% from preoperative density in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of significant sight-threatening DMD after phacoemulsification was 0.044% to 0.52% [ 14 , 15 ]. Improper operation of instrument entry into the anterior chamber is the most significant cause of DMD following phacoemulsification [ 18 ]. Although postoperative visual acuity and corneal thickness returned to normal levels afterward, the corneal endothelial cell density decreased by 30% from preoperative density in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This was endorsed by the findings of Wang and colleagues who also indicated that the inappropriate hydration of corneal side ports might result in DMD. 7 We recommend being gentle and vigilant while hydrating side ports. Over hydration should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Improper surgical manipulations including anteriorly placed, shelved, or small incisions, suboptimal quality of the surgical instruments (especially use of blunt microkeratomes), or engagement of the DM during irrigation/aspiration, and antibiotic, saline, or viscoelastic material injection into the space between the deep stroma and DM are primary reasons for intraoperative DMD. 16 Ti and colleagues 7 described several risk factors for post-operative DMD including older age, grade 4 or 5 nuclear sclerotic cataract, pre-existing endothelial disease, and corneal oedema on the first post-operative day. On the other hand, genetically related weak or abnormal adhesions between the stroma and DM also underlie anatomic predispositions for the development of intraoperative or postoperative DMD.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of clinically significant DMD associated with cataract surgery has been reported as 0.05 % to 0.5 %. 1 In these cases, DMD is mostly seen during surgery or in the early post-operative period associated with surgical technique, surgical equipment or genetic factors 1–4…”
Section: Introductionmentioning
confidence: 99%